Long-term risk of sudden cardiac death in hypertrophic cardiomyopathy - a cardiac magnetic resonance outcome study. (8th February 2021) - Seitz, A; Greulich, S; Herter, D; Guenther, F; Probst, S; Bekeredjian, R; Gawaz, M; Sechtem, U; Mahrholdt, H
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Robert Bosch Stiftung; Deutsche Forschungsgemeinschaft Background: Sudden cardiac death (SCD) is an appalling complication of hypertrophic cardiomyopathy (HCM). There is an ongoing discussion about the optimal SCD risk stratification strategy in HCM since established SCD risk models have suboptimal discriminative power. Objective: To evaluate the prognostic value of late gadolinium enhancement (LGE) cardiac magnetic resonance (CMR) for SCD risk stratification compared to the ESC SCD risk score and traditional SCD risk factors in an >10-year follow-up study. Methods: 220 consecutive patients with HCM and LGE-CMR were enrolled. Follow-up data was available in 203 patients (median age 58 years, 61% male) after a median follow-up period of 10.4 years. Results: LGE was present in 70% of patients with a median LGE amount of 1.6%, the median ESC 5-year SCD risk score was 1.84. In the overall cohort, SCD rates were 2.3% at 5 years, 4.8% at 10 years, and 15.7% at 15 years, independent from established risk models. A LGE amount of >5% (LV mass) portends the highest risk for SCD with SCD prevalences of 5.5% at 5 years, 13.0% at 10 years and 33.3% at 15 years. Conversely, patients with no or ≤5% LGE amount (of LV mass) have favorable prognosis. Conclusions: LGE-CMR in HCM patients allows effective 10-year SCD risk stratification beyond established risk factors. LGE amount might be added to established risk models to improve its discriminatory power. Specifically, patients with >5% amount of LGE should be carefully monitored and might be adequate candidates for primary prevention ICD during the clinical long-term course.